EP.WE.330The role of computerized tomography scan in 2 week wait colorectal pathway during COVID-19 pandemic. (28th October 2021) - Ali, Muhammad; Castelhano, Rute; Theofilis, Aris; Wass, Emily; Alexander, Roderick; Owais, Anwar
Abstract: Aims: The standard way to investigate patients referred on the two week wait colorectal cancer (2WW) pathway is to do a colonoscopy when patients are deemed fit. Due to limited endoscopy services during the COVID-19 lockdown period, we performed computerized tomography scan of thorax, abdomen and pelvis (CT TAP) for all fast-track colorectal referrals in addition to colonoscopy when service restarted. The aim of this study is to assess the benefit of CT scan in this group of patients. Methods: All 2WW patients referred to our district general hospital from April 1, 2020 to July 31, 2020 were included in the study. The data were collected retrospectively from GP referral forms and the electronic patient records. Patient demographics, presenting complaints, investigations, diagnosis and treatment were recorded. Results: A total of 658 patients were included in the study. The commonest presenting complaint was change in bowel habit (62.5%). A total of 414 colonoscopies, 347 CT TAP, 89 flexible sigmoidoscopies and 37 CT colonography were performed. 194 patients had both CT TAP and colonoscopy and another 32 patients had both CT TAP and flexible sigmoidoscopy showing that 34% of patients had both CT TAP and endoscopy. 41 patients were diagnosed with colorectal malignancy (6.2%) and 120 had polyps (18%). CT TAP missed 3 colorectal cancers but picked up 28 patients (4.3%) diagnosed with extra-colonic tumours. Conclusions: Colonoscopy remains the gold standard for investigating colorectal cancer. However, CT scan have their value in diagnosing extra-colonic tumours in this specific group of patients.